Regulation of phasin expression and polyhydroxyalkanoate (PHA) granule formation in Ralstonia eutropha H16 - Potter, Markus; Madkour, Mohamed H; Mayer, Frank; Steinbuchel, Alexander (Microbiology (Society for General Microbiology), 2002)
Institut für Mikrobiologie der Westfälischen Wilhelms-Universität Münster, Corrensstrasse 3, D-48149 Münster, Germany 1 Institut für Mikrobiologie und Genetik der Georg-August-Universität Göttingen, Grisebachstrasse 8, D-37077 Göttingen, Germany 2 Author for correspondence: Alexander Steinbüchel. Tel: +49 251 8339821. Fax: +49 251 8338388. e-mail: steinbuatuni-muenster.de Regulation of expression of the phasin PhaP, which is the major protein at the surface of polyhydroxyalkanoate (PHA) granules in Ralstonia eutropha H16, was studied and analysed at the molecular level. The regulation of PhaP expression is achieved by an autoregulated repressor, which is encoded by phaR in R. eutropha. The occurrence of PhaR homologues and the organization of phaR genes was analysed in detail in 29 different bacteria. Three kinds of molecule to which PhaR binds were identified in cells of R. eutropha , as revealed by gel-mobility-shift assays, DNaseI footprinting, cell fractionation, immunoelectron microscopy studies employing anti-PhaR antibodies raised against purified N-terminal hexahistidine-tagged PhaR and in vitro binding studies employing artificial PHA granules. PhaR binds upstream of phaP at two sites comprising the transcriptional start site plus the -10 region and a region immediately upstream of the -35 region of the 70 promoter of phaP , where two imperfect 12 bp repeat sequences (GCAMMAAWTMMD) were identified on the sense and anti-sense strands. PhaR also binds 86 bp upstream of the phaR translational start codon, where the 54 -dependent promoter was identified. PhaR also binds to the surface of PHA granules. In the cytoplasm of a phaR Km mutant of R. eutropha H16, increased quantities of PhaP were detected and the cells formed by this strain were much smaller and had many more PHA granules present than the wild-type. These data support the following model for the regulation of phaP expression. Under cultivation conditions not permissive for PHA biosynthesis or in mutants defective in PHA biosynthesis, PhaR binds to the phaP promoter region and represses transcription of this gene. After the onset of PHA biosynthesis, under conditions that are permissive for the formation of nascent granules, PhaR binds to PHA granules and phaP is transcribed. At the later stages of PHA accumulation, PhaR no longer binds to the granules and the transcription of phaP is again repressed. In addition to this, phaR expression is subject to autoregulation. Excess PhaR that has not bound to the phaP upstream region or to PHA granules binds to the phaR upstream region, thereby repressing its own transcription. Keywords: phaR , phaP regulation, repressor, inclusion bodies, autoregulation of phaR Abbreviations: GARG, goat-anti-rabbit IgGgold; His 6 , hexahistidine; MM, mineral salts medium; PHA, polyhydroxyalkanoate; PHB, polyhydroxybutyrate; poly(3HB), poly(3-hydroxybutyrate)